1996
DOI: 10.1136/jmg.33.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Nijmegen breakage syndrome.

Abstract: Nijmegen breakage syndrome (NBS), a rare autosomal recessive condition also known as ataxia telangiectasia (AT) variants VI and V2, is characterised by microcephaly, typical facies, short stature, immunodeficiency, and chromosomal instability. We report the clinical, immunological, chromosomal, and cell biological findings in 42 patients who are included in the NBS Registry in Nijmegen. The immunological, chromosomal, and cell biological findings resemble those in AT, but the clinical findings are quite differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
111
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(113 citation statements)
references
References 19 publications
2
111
0
Order By: Relevance
“…8 In 40% of the patients, in fact, a malignancy occurs before the age of 21. 9 About 90% of the NBS patients are of Slav origin and carry the major founder mutation 657del5 in exon 6; eight distinct mutations have been found in families of different ethnic origin. 10 -12 In NBS cells, chromatid and chromosome breakages, acentric fragments, asymmetrical multiradial configurations among nonhomologous chromosomes and sporadic or clonal translocations and inversions are present.…”
Section: Introductionmentioning
confidence: 99%
“…8 In 40% of the patients, in fact, a malignancy occurs before the age of 21. 9 About 90% of the NBS patients are of Slav origin and carry the major founder mutation 657del5 in exon 6; eight distinct mutations have been found in families of different ethnic origin. 10 -12 In NBS cells, chromatid and chromosome breakages, acentric fragments, asymmetrical multiradial configurations among nonhomologous chromosomes and sporadic or clonal translocations and inversions are present.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Due to the overlap of clinical and cellular features of patients with ataxia telangiectasia (AT), NBS was described as an AT variant syndrome until the underlying gene product mutation was identified. [3][4][5] Cells from both AT and NBS patients show increased sensitivity to ionizing radiation (IR), genomic instability and cell cycle checkpoint defects following DNA damage, 6,7 suggesting that both gene products participate in the same DNA damage response pathway.…”
Section: Introductionmentioning
confidence: 99%
“…NBS cells cultured in vitro are deficient in the response to treatment with DNA DSB-inducing agents such as ionizing radiation and radiomimetic compounds. These defective responses include reduction in colony-forming ability post-irradiation, a failure to inhibit DNA synthesis in response to acute doses of radiation, and an increased frequency of chromosomal aberrations (4,5). Positional cloning studies in NBS families and functional complementation studies identified a single gene, NBS1, which is mutated in most patients with NBS (6,7).…”
mentioning
confidence: 99%